2023
DOI: 10.3390/su152014739
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Students’ Push and Pull Motivations to Visit Rural Educational Tourism Sites in China

Feifei Yang,
Rajenthyran Ayavoo,
Norazlin Ab Aziz

Abstract: Educational tourism in rural areas promotes local employment, economic development, and poverty alleviation. Given that there is a lack of research on emerging and developing nations, this study adopted the viewpoint of an emerging country and empirically demonstrates the relationships of consumer behavior with education tourism in rural areas. In particular, the study focused on push-pull motivation factors and loyalty. The mediating role of overall satisfaction on the relationship between push-pull motivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Finally, this study identified various proposals for the future to counteract the crisis experienced by traditional trades, as a reflection of rural abandonment. In addition, it is particularly important to know the opinion of university students in this aspect, since they represent a generation capable of actively participating in the improvement and protection of their socio-cultural environment [84,104,105].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study identified various proposals for the future to counteract the crisis experienced by traditional trades, as a reflection of rural abandonment. In addition, it is particularly important to know the opinion of university students in this aspect, since they represent a generation capable of actively participating in the improvement and protection of their socio-cultural environment [84,104,105].…”
Section: Discussionmentioning
confidence: 99%
“…For example, some of the reviewed studies (Matiza and Slabbert, 2023;Matiza and Kruger, 2022) analysed domestic tourists travel motivation from a COVID-19 perspective, making them inefficient in informing sustainable domestic tourism development. While others focused on single attractions (Moliner-Tena et al, 2023), tiny locations (Duong et al, 2023) and a single type of traveler (Yang et al, 2023). The present study attempts to fill these gaps.…”
Section: Pull Motivationsmentioning
confidence: 96%